2020
DOI: 10.1186/s13075-020-02184-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the use of analgesic drugs 1 year after joint replacement: a single-center analysis of 13,000 hip and knee replacements

Abstract: Background: Pain persists in a moderate number of patients following hip or knee replacement surgery. Persistent pain may subsequently lead to the prolonged consumption of analgesics after surgery and expose patients to the adverse drug events of opioids and NSAIDs, especially in older patients and patients with comorbidities. This study aimed to identify risk factors for the increased use of opioids and other analgesics 1 year after surgery and focused on comorbidities and surgery-related factors. Methods: Al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
0
13
1
Order By: Relevance
“…The association found in patients with diabetes mellitus may be because they also suffer from diabetic neuropathy, which results in analgesia, paresthesia, and pain, which could yield to specific analgesics and eventually to opioids, particularly tramadol [ 33 ]. Osteoarthritis is a chronic pain disorder, which may eventually require, depending on the intensity of the symptom, analgesics capable of relieving pain when acetaminophen or NSAIDs fail to do so [ 34 , 35 ]. Furthermore, it has already been observed that epilepsy can be a predictor of subsequent opioid use, particularly in patients with a painful knee and hip disorders [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The association found in patients with diabetes mellitus may be because they also suffer from diabetic neuropathy, which results in analgesia, paresthesia, and pain, which could yield to specific analgesics and eventually to opioids, particularly tramadol [ 33 ]. Osteoarthritis is a chronic pain disorder, which may eventually require, depending on the intensity of the symptom, analgesics capable of relieving pain when acetaminophen or NSAIDs fail to do so [ 34 , 35 ]. Furthermore, it has already been observed that epilepsy can be a predictor of subsequent opioid use, particularly in patients with a painful knee and hip disorders [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, attempts have been made to identify patients undergoing THA or TKA who do not benefit from surgery as well as expected and who continue to use analgesic drugs after surgery [4, 16, 22, 39]. Earlier, we found that analgesic drug consumption is reduced after hip and knee arthroplasty at the population level [36], and that obesity, a higher number of comorbidities, gender (women more than men), and preoperative use of analgesics were associated with the postoperative use of opioids, NSAIDs, or acetaminophen [38]. Previous studies have almost exclusively focused on opioid consumption, although psychiatric disorders, worse preoperative pain, and catastrophizing have also been associated with increased consumption of opioids after joint arthroplasty [4, 12, 22, 24, 25, 27, 32, 42, 43].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a higher BMI was associated with more frequent painkiller consumption at 12 months. This observation was not surprising, since obesity is associated with a prolonged use of painkillers at 12-month follow-up even after total joint arthroplasty [ 19 ].…”
Section: Discussionmentioning
confidence: 99%